High Precision Phase Noise Analysis Based on a Photonic-Assisted Microwave Phase Shifter Without Nonlinear Phase Distortion - Jian Wang; Wenting Wang; Renheng Zhang; Bei Chen; Dechao Ban; Ya Jin; Keqi Cao; Yu Liu; Ninghua Zhu (IEEE Photonics Journal, 2023)
We propose and demonstrate a high-precision phase noise analysis method based on a photonic-assisted microwave phase shifter (MPS) without nonlinear phase distortions (NPD). The proposed scheme utilizes a dual parallel Mach Zehnder modulator (DPMZM) and an optical bandpass filter (OBPF) to implement the photon-assisted microwave phase shifter. To avoid additional frequency noise induced by frequency fluctuations of the optical carrier, we employ a dispersion compensation photonic delay line as the delay line component. The MPS operates in the optical single sideband modulation (OSSB) mode with even-order sideband suppression, allowing continuous phase tuning over the entire $\mathbf { 360^{° }}$ range and eliminating NPD commonly encountered in traditional microwave photonic phase shifters. Experimental results demonstrate significant improvements in the phase and magnitude responses of the MPS without NPD compared to those with NPD. The proposed system exhibits long-term stability, with phase drift and amplitude drift of less than $\mathbf {5^{° }}$ and 1 dB, respectively, over continuous operation for more than 1500 seconds. We successfully measured microwave signals at the frequency of 8 GHz, 10 GHz, and 12 GHz with phase noise of $-$ 66.7, $-$ 65.5, and $-$ 62.1 dBc/Hz at 10 kHz offset frequency without resetting the proposed system. The method could be used to characterize electronic and photonic oscillators, which is highly reconfigurable and widely tunable.